2021
DOI: 10.3762/bjoc.17.92
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced post-modification of graphitic carbon nitride-embedded hydrogels: synthesis of 'hydrophobic hydrogels' and pore substructuring

Abstract: Hydrogels are a special class of crosslinked hydrophilic polymers with a high water content through their porous structures. Post-modifications of hydrogels propose an attractive platform so that a variety of fresh functions, which are not arising from initial monomers, could be accessible on a parental network. Photoinduced post-modification of hydrogels by embedding semiconductor nanosheets would be of high interest and novelty. Here, a metal-free semiconductor graphitic carbon nitride (g-CN)-embedded hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…In addition to "hydrophobic hydrogel" fabrication, parental g-CN embedded hydrogel is swollen by various acrylate monomers via immersion, and, under visible-light irradiation, secondary polymer networks were formed, resulting in "pore substructuring". 88 CO 2 can help forming porosity in macroscale structures, as shown in fabrication of g-CN-immobilized alginate porous gel beads. Aqueous dispersion of g-CN nanosheets (CNNSs) were mixed with sodium alginate (NaAlg) solution containing sodium dodecyl sulfate (SDS) and sodium bicarbonate (NaHCO 3 ) under agitation until a foamy solution is obtained.…”
Section: ■ Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to "hydrophobic hydrogel" fabrication, parental g-CN embedded hydrogel is swollen by various acrylate monomers via immersion, and, under visible-light irradiation, secondary polymer networks were formed, resulting in "pore substructuring". 88 CO 2 can help forming porosity in macroscale structures, as shown in fabrication of g-CN-immobilized alginate porous gel beads. Aqueous dispersion of g-CN nanosheets (CNNSs) were mixed with sodium alginate (NaAlg) solution containing sodium dodecyl sulfate (SDS) and sodium bicarbonate (NaHCO 3 ) under agitation until a foamy solution is obtained.…”
Section: ■ Hydrogelsmentioning
confidence: 99%
“…It is demonstrated that resulting “hydrophobic hydrogel” can be employed for agricultural applications to simulate a nutrition release system in a controlled way. In addition to “hydrophobic hydrogel” fabrication, parental g-CN embedded hydrogel is swollen by various acrylate monomers via immersion, and, under visible-light irradiation, secondary polymer networks were formed, resulting in “pore substructuring” …”
Section: Hydrogelsmentioning
confidence: 99%
“…[19,20] The present review deals with another way to change the properties of hydrogels apart from type of bonding, shape, and mechanical properties, namely, via composition. A variation of composition can be introduced via functionalization (also with spatial control), [21,22] for example, but also by introduction of compartments. The variation of hydrogel composition puts hydrogels on a new level of complexity giving rise to novel applications and tuning of hydrogel properties.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 2. Schematic overview of g-C 3 N 4 -embedded hydrogel fabrication and its subsequent photoinduced post-modifications[8]. Copyright 2021, Beilstein Journal of Organic Chemistry.…”
mentioning
confidence: 99%